2021
DOI: 10.1097/acm.0000000000004271
|View full text |Cite
|
Sign up to set email alerts
|

The Performance and Trajectory of Medical Students With Disabilities: Results From the Pathways Project

Abstract: The number of medical students disclosing disabilities and requesting accommodations is increasing, [1][2][3] prompting new questions about performance of students with disabilities (SWD) on United States Medical Licensing Exam (USMLE) examination scores and to match into residency. Historical data on SWD suggest lower performance and extended time to graduation, 4,5 but little is known about whether category of disability and accommodation on the Step 1 examination impact performance, time to graduation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
2
19
0
Order By: Relevance
“…In contrast, those who receive accommodations are 6 points lower than the average population ( 14). This information further proves that barriers remain for competent students when not given their proper accommodations (14,16,12). Therefore, there is a need to investigate the medical education learning environment to ensure robust support systems for these students (16).…”
Section: Lack Of Understanding Of Accommodation Needs [mentioning
confidence: 65%
See 3 more Smart Citations
“…In contrast, those who receive accommodations are 6 points lower than the average population ( 14). This information further proves that barriers remain for competent students when not given their proper accommodations (14,16,12). Therefore, there is a need to investigate the medical education learning environment to ensure robust support systems for these students (16).…”
Section: Lack Of Understanding Of Accommodation Needs [mentioning
confidence: 65%
“…A recent 2021 study by Meeks et al addressed the lack of information about whether or not accommodations on USMLE Step 1 impact performance, time to graduation, and match rates. The information discussed in the Searcy and Tehrani articles left the area of students being accommodated within the medical school and on USMLE Step exams open for more investigation (14,22,25). Within the study, 69% of students were identi ed as having cognitive/learning disabilities (14).…”
Section: Disability Prevalencementioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, obtaining approval for accommodations on USMLE exams can be difficult, as evidenced by recent litigation [ 14 – 17 ]. SWD score lower on Step-1 than their non-disabled peers [ 6 , 18 , 19 ], A recent multi-site study suggested that approximately 25% of students with disabilities in their sample were approved for accommodation on Step-1. Students in this study who received accommodation on Step-1 performed better than those without accommodation, by an average of 6 points.…”
Section: Introductionmentioning
confidence: 99%